Correlation of Sex, Age and Carcass Weight of Simmental-PO Cattle in the Slaughterhouse, Sukorejo District, Blitar City, East Java - Salnan Irba Novaela Samur; Agustina Widyasworo Kunharjanti (Universitas Islam Balitar, 2023)
The objective of this study is to describe the correlation between age and sex in relation to the carcass weight of Simental-PO cattle that are slaughtered at the slaughterhouse (RPH) in the Sekorejo District of Blitar City, located in East Java. The investigation was conducted in July of 2023. The study utilized 20 male and 10 female Simental-PO cattle that were slaughtered at the Sukorejo District Slaughterhouse, located in the Blitar Regency. The employed study methodology entails the utilization of the direct observation approach. The obtained data was subsequently analyzed using SPSS 22 software and afterwards subjected to statistical tests like the Pearson Bivariate Correlation Test and Multiple Linear Regression Test. The findings obtained from the bivariate Pearson correlation analysis indicated a statistically significant correlation between sex and carcass weight. However, no statistically significant correlation was seen between age and carcass weight. The regression analysis reveals that the variables of gender and age account for only 31.3% of the variation in carcass weight. The resulting regression equation is Y = 17.887 + 69.943X1 + 15.994X2. The research indicated a significant correlation between gender and carcass weight, while age does not exhibit a significant correlation with carcass weight. Therefore, further studies are warranted to explore the influence of factors besides age and gender on Simmental-PO beef carcass weight.